The Influence of Audit Fee, Audit Tenure, and Auditor Competency on Audit Quality: A Systematic Review - Fadila, Ega; Ramadhyani, Yesica; Saputri, Yunita; Manurung, Herlina (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Financial audit reports play a crucial role in corporate decision-making, and their quality is impacted by various factors such as audit fees, audit tenure, and auditor competency. Audit fees refer to the costs associated with audit services, audit tenure signifies the duration of the audit firm's responsibility, and auditor competency encompasses the auditor's knowledge, skills, and attitudes. This study employs a systematic review approach, analyzing articles downloaded from the Google Scholar online database covering journals published from 2019 to 2023 using keywords like audit fee, audit tenure, auditor competency, and quality of financial audit reports. The research incorporates 10 quantitative journals, with 5 employing linear regression analysis, 4 using logistic regression analysis, and 1 utilizing the partial least squares method. The findings reveal that a majority of the journals demonstrate a positive and significant correlation between audit fees, audit tenure, auditor competency, and the quality of audit reports. Nonetheless, a few articles assert the absence of a relationship between audit fees, audit tenure, and audit quality. In summary, public accounting firms should regularly assess and formulate strategies concerning audit fees, audit tenure, and auditor competency to enhance client value by producing high-quality, accurate, and dependable financial audit reports.